impact of online games and students' learning interest on english learning achievement - rospin, rospin; Imran, Fathurrahman (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to examine whether there is an effect of using online games and students' interest on English learning achievement at SMAN 1 Pringgasela. Sampling used a total sampling technique with a total of 20 people. This study uses two independent variables, namely online games (X1) and student interest (X2), while the dependent variable is learning achievement (Y). The data used in this study is primary data in the form of a questionnaire with 20 respondents. This research method uses ex post facto. The data analysis technique used in this study was simple regression analysis. The results of this study note the F value of 1.390 < compared to the F-table of 3.59. So, it can be concluded that H0 is accepted and Ha is rejected, which means that there is no significant effect between online games (X1) and interest (X2) on student achievement (Y).